EXECUTIVE PROFESSIONAL DEVELOPMENT PLATFORM ’MOTHERSHIP’ IN HEA AND PUBLIC NGO RESEARCH SYNERGY - Kropáč, Jiří (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
As academics, we cannot influence our students' social and economic early conditions easily. Family roots and social-economic parents' position of upcoming students to HEA institution is given. Education purposes are not just a degree. Pathway to those achievements in HEA is crooked and theoretical content transferred by lectures' good faith in systematic preparation leads to curricula fulfilment only. The HEA level is dealing with various challenges daily. Those hidden challenges may be invisible insurances of bright future for students in the non-ideal institutional world, balancing on the curricular theoretical framework without functional connectivity. A starting position of our PhD students is poorly supported, especially in the EU context policy for humanities in an early carrier trajectories of research skills development. The endeavour to transfer an excellent practical outputs, developed by students in institutional conditions, research and practice go hand in hand. This analytical study introduces mixed methodological design Interpreting the results of content analysis of interviews conducted with students in PhD programmes and proposes strategies for the best practice transfer to a legal NGO entity. Firstly, monitoring questionnaire analysis helps to create essential structure of the interviews with PhD students' according to their needs. Outputs of this analysis reinforced the transfer of non-governmental professional support for early carrier academics already since 2018. Moreover, it identifies factors of early academics' identity belonging under institutional support curricula. Secondly, National policy content analysis points in 2022 to fundamental improvements in early carrier academics institutional policy, based on practice connection in scientific research HUB. Although, presented outputs are new outcomes of pilot cooperation with NGOs' association Máma studuje z.s., they already represent an applied output for further scientific students' development and suggest how to enrich entrepreneurship with research and teaching excellence to make an impact on other societies out of academia.